ChemInform Abstract: Oxygen Trapped by Rare Earth Tetrahedral Clusters in Nd4FeOS6: Crystal Structure, Electronic Structure, and Magnetic Properties. Issue 39 (September 2015) - Lin, Qisheng; Taufour, Valentin; Zhang, Yuemei; Wood, Max; Drtina, Thomas; Bud'ko, Sergey L.; Canfield, Paul C.; Miller, Gordon J.
Abstract Single crystals of Nd4FeOS6 are grown from an Fe‐S eutectic solution using a mixture of the elements in the molar ratio of Nd:Fe:S = 4:55:41 (alumina crucible, heating to 1150 °C over 12 h; cooling to 1000 °C with a rate of 1 °C/h).